2015
DOI: 10.1016/j.jnucmat.2015.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical properties and oxygen transport in the (U ,Pu1−)O2 lattice

Abstract: Using molecular dynamics, the thermophysical properties of the (U x ,Pu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 44 publications
13
62
0
Order By: Relevance
“…upon heating in the 300-4500 K range, with the reported experimental data by Fink et al [27][28] At this point it is important to note, the potential set used in this study for ThO2, UO2 and PuO2 efficiently reproduces experimentally reported elastic constants [36] and thermal properties [5,6,36,40,41]. Therefore, incorporation of many-body effects by EAM in conjunction with…”
Section: Figure 3(a) Shows the MD Calculated Change In Enthalpy (H(t)supporting
confidence: 78%
See 2 more Smart Citations
“…upon heating in the 300-4500 K range, with the reported experimental data by Fink et al [27][28] At this point it is important to note, the potential set used in this study for ThO2, UO2 and PuO2 efficiently reproduces experimentally reported elastic constants [36] and thermal properties [5,6,36,40,41]. Therefore, incorporation of many-body effects by EAM in conjunction with…”
Section: Figure 3(a) Shows the MD Calculated Change In Enthalpy (H(t)supporting
confidence: 78%
“…The most recent empirical potential form for ThO2, UO2 [35] and PuO2 [36] as well as their MOX [37] which is employed in this study, combines a pair-wise with a many body interaction term.…”
Section: Empirical Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a many-body potential has been developed [3e5] that is capable of describing the temperature dependence of the UO 2 bulk modulus. Additionally, the parameter set accurately reproduced the elastic constants and thermal expansion of CeO 2 , ThO 2 , UO 2 , NpO 2 , PuO 2 [5], AmO 2 and CmO 2 . (Note that the PuO 2 parameters have been modified [5] since the original potential set to reproduce the melting point.)…”
Section: Introductionmentioning
confidence: 73%
“…Additionally, the parameter set accurately reproduced the elastic constants and thermal expansion of CeO 2 , ThO 2 , UO 2 , NpO 2 , PuO 2 [5], AmO 2 and CmO 2 . (Note that the PuO 2 parameters have been modified [5] since the original potential set to reproduce the melting point.) Through the later addition of mixed cationecation parameters it has become possible to examine solid solutions of actinide oxides [4].…”
Section: Introductionmentioning
confidence: 73%